Polychlorinated Biphenyls in the Centralized Wastewater Treatment Plant in a Chemical Industry Zone: Source, Distribution, and Removal - Min Yao; Zhongjian Li; Xingwang Zhang; Lecheng Lei (Journal of Chemistry)
Polychlorinated biphenyls (PCBs) could be dissolved in wastewater or adsorbed on particulate. The fate of PCBs in wastewater is essential to evaluate the feasibility of wastewater treatment processes and the environmental risk. Here dissolved and adsorbed concentrations of twenty concerned PCB congeners and total PCBs have been measured in the centralized wastewater treatment plant of a chemical industry zone in Zhejiang, China. It was found that the dyeing chemical processes were the main source of PCBs, which contributed more than 13.6%. The most abundant PCB was PCB-11 in the liquid and solid phase of each treatment stage, accounting for more than 60% of the total 209 PCBs. Partitioning behavior of PCBs between the dissolved and adsorbed phases suggested that Di-CBs were the dominant isomers (>70%) and more than 89.8% of them was adsorbed on the particles and sludge. The total removal efficiency of ∑209 PCBs was only 23.2% throughout the whole treatment process. A weak correlation was obtained between the individual PCB concentration and their log Kow in primary sedimentation, anaerobic hydrolysis, aerobic bioprocess stage, and the whole treatment process.